The Implementation of Religious Moderation in West Sumatra from the Perspective of Maqāsid Sharī'ah - Rusyaida D; Noor Fadlli Marh; M Taufiq; M Fadhli; Sabri (Esensia: Jurnal Ilmu-Ilmu Ushuluddin)
Religious moderation is an important issue in maintaining harmony and cohesion within the diverse society of West Sumatra. The application of the philosophy Adat Basandi Syara’, Syara’ Basandi Kitabullah (ABS-SBK) as a basis for religious moderation in West Sumatra is often viewed negatively by some, who perceive it as intolerance. This study aims to clarify and counter these negative perceptions through a qualitative approach with a case study method in West Sumatra. Data were collected through in-depth interviews with religious leaders, community leaders, as well as document analysis and participatory observation. The findings show that the implementation of religious moderation aligns with the concept of religious moderation in Islam, known as Wasatiyatul Islam as a distinctive Islamic quality, both in terms of showing moderation in differing religious interpretations with mutual respect for varied practices, as well as between different religions and ethnicities. From a Maqashid Shariah perspective, religious moderation in West Sumatra successfully safeguards and protects the five key aspects: religion (ad-din), intellect (al-‘aql), life (an-nafs), lineage (an-nasl) from conflict and violence, and property (al-mal). Managing communal assets through shared economic activities also strengthens inter-community relations. This study concludes that the implementation of religious moderation in West Sumatra, from a Maqashid Shariah perspective, can serve as an effective model for fostering social harmony in a pluralistic society.